Exploring Role Play in Early Childhood Education: A Bibliometric Analysis Based on Scopus Data - Nazar, Lailatun; Fitri, Ruqoyyah; Jannah, Miftakhul; Kristanto, Andi; Rinakit Adhe, Kartika (Perkumpulan Pengelola Jurnal (PPJ) PAUD Indonesia, 2025)
This research examines trends and developments in the study of role play in early childhood education through a bibliometric analysis based on Scopus data. The main focus is a systematic mapping of academic literature that addresses the contribution of role-playing to children's cognitive, social-emotional and language development. The approach used was descriptive-quantitative bibliometric analysis, which included identification, screening, eligibility evaluation and inclusion of scientific publications from 2015 to 2024. A total of 42 documents (35 articles and 7 books) that met the inclusion criteria were analyzed using VOSviewer, Microsoft Excel, and Publish or Perish software. The results showed that the peak of publications occurred in 2022, before experiencing a decline in the following years. In terms of collaboration, studies were dominated by countries such as the United Kingdom and Australia, which were noted to appear most frequently in author affiliations. Thematic cluster analysis revealed several major foci with dominant keywords such as “role play,” “child language,” and “play.” In addition, a number of new keywords were found that reflect the direction of future research developments. This study provides a comprehensive overview of the scientific landscape related to role play, and can serve as an important reference for researchers, educational practitioners, and policy makers in designing play-based early childhood education interventions.